The Impact of Service Quality and Pricing on Customer Satisfaction: An Analysis of Pelni Ships at Makassar Port - Rasulong, Ismail; Rifaldi, Rifaldi; Yusuf, Muhammad (Universitas Muhammadiyah Makassar, 2025)
Understanding the factors that influence customer satisfaction is crucial for transportation companies to enhance their services and retain customers. This study aims to examine the impact of service quality and price on customer satisfaction, utilizing a sample of 239 passengers of Pelni ships at Makassar Port. Utilizing multiple linear regression analysis, data were collected and analyzed to determine the relationship between these variables. The findings indicate that neither service quality nor price significantly affects customer satisfaction at the 5% significance level. The unstandardized coefficients are 0.035 for service quality and 0.301 for Price, with significance values of 0.242 and 0.182, respectively. The model explains 31.2% of the variation in customer satisfaction (R Square = 0.312), with an Adjusted R Square of 0.306. However, 68.8% of the variation is attributed to other factors not included in this study. The study's limitations include the exclusion of other potential influencing factors and a moderate sample size. Future research should explore additional variables, such as perceived value and customer loyalty, using larger samples and more comprehensive methods. Companies should continue enhancing service quality and reviewing pricing strategies to boost customer satisfaction and loyalty.